(untitled) (Canadian Journal of Counselling and Psychotherapy, 2017)
The use of neuroimaging has become increasingly popular among applied psychological researchers. However, when implementing a neuroimaging study in counselling psychology, several conceptual and methodological issues that may threaten internal or external validity must be considered. Although neuroimaging methods hold promise as a tool for counselling psychologists to utilize as we move toward a greater emphasis on science-based practice, important limitations must be addressed at the conceptual (e.g., the reverse inference problem, the danger of neurorealism, and lack of ecological validity) and methodological (e.g., preprocessing, design of experimental tasks, multiple comparisons correction) levels. We discuss the advantages and limitations of the application of neuroimaging to the field of counselling psychology and provide recommendations for those who wish to conduct research in this area.